Adoption and Diffusion of Power Tillers in Bangladesh (Bangladesh Journal of Agricultural Research, 2012)
The present study examines the extent of adoption of power tillers (PT) in  Bangladesh and analyzes the variation in adoption across regions and across farms in selected areas to investigate the justification for wider use of power tillers. Primary and secondary data were used. Primary data were collected from 267 sample farmers from eight villages of four upazilas of four districts using proportionately stratified random sampling technique. Secondary data were collected from different published sources. The average growth rate of power tillers in Bangladesh was 21.0 percent during 1993-2003. Power tillers are unevenly distributed all over the country. The highest and the lowest adoption of power tillers were 44.4 and 3.6 percent in Rajshahi and Barisal divisions respectively. The percentage of area cultivated under power tiller is 69.6. Multiple regression analysis indicates that there is a significant relationship between number of PT and credit availability. The credit availability may be a decisive factor in increasing cropping intensity which requires reduction of turnaround time. Irrigated area, number of small farm holdings and credit availability are found to have significant and positive association with intensity of power tiller use in different regions of Bangladesh. Analysis of Logit Model applied to farm level data indicates that the educational level and income surplus of farmers have significant positive relationship with ownership of power tillers. The coefficients of adult family members and number of draught power owned by the farmers are however found to be significantly negative. The number of power tiller is increasing with the decreasing of draught animal power. Thus credit should be provided to the farmers and owners of all regions of the country  to buy power tillers to adopt evenly to increase crop production profitably. DOI: http://dx.doi.org/10.3329/bjar.v37i2.11234 Bangladesh J. Agril. Res. 37(2): 307-325, June 2012